The System and Content of Administrative-Legal Coercion Applied to the Parties Relations in the Sphere of Securities Market - Igor Evgenievich Taranov (Управленческое консультирование)
The article discusses the types of measures of administrative legal compulsion applied by authorized bodies to the participants of relations in the sphere of securities market, their classification is given, the grounds and purpose of use, highlights the General and specific features of measures of administrative and legal coercion, traces the evolution of the legislation on administrative offences in the sphere of securities market, analyzes the Institute of insignificance of an administrative offence, examined the correlation of administrative fines value of fines established by the criminal code, for committing similar wrongful acts, the necessity of making changes in the system of administrative penalties provided for in the administrative code for administrative offenses in the sphere of securities market.